Overcoming Academic Procrastination for College Student - Lulu Fatihatul Uyun; Ilfiandra Ilfiandra; Anne Hafina (Psychosophia: Journal of Psychology, Religion, and Humanity, 2023)
Abstract; Academic procrastination is an individual's deliberate delay in starting, working on, and completing academic tasks. Procrastination is caused by finding it difficult to do tasks, when given a task load, a procrastinator tends to delay and prefer to do things he likes. This article aims to examine the handling of academic procrastination. The research method used study of literature on how to overcome academic procrastination from relevant sources. The data collection technique collect several previous studies and then analyze and conclude them conclusion is obtained regarding the prevention of academic procrastination. The data sources used are articles, journals, and books that discuss academic procrastination. Data sources are obtained from various search sites such as Google Scholar, Science Direct, SAGE Pub, etc. The results showed that academic procrastination can be overcome by increasing self-regulation, making plans, setting schedules based on priorities, preparing thoroughly, doing tasks step by step, upgrading knowledge and skills, identifying constraints, motivating yourself. Keyword; Academic procrastination, College student, Overcoming. Abstrak; Penundaan akademik adalah penundaan yang disengaja individu dalam memulai, mengerjakan, dan menyelesaikan tugas akademik. Penundaan disebabkan karena merasa sulit mengerjakan tugas, ketika diberi beban tugas, seorang penunda cenderung menunda-nunda dan lebih suka melakukan hal-hal yang disukainya. Artikel ini bertujuan untuk mengkaji penanganan prokrastinasi akademik. Metode penelitian yang digunakan adalah studi kepustakaan tentang cara mengatasi prokrastinasi akademik dari sumber-sumber yang relevan. Teknik pengumpulan data mengumpulkan beberapa penelitian sebelumnya kemudian dianalisis dan disimpulkan bahwa diperoleh kesimpulan mengenai pencegahan prokrastinasi akademik. Sumber data yang digunakan adalah artikel, jurnal, dan buku yang membahas tentang prokrastinasi akademik. Sumber data diperoleh dari berbagai situs pencarian seperti Google Scholar, Science Direct, SAGE Pub, dll. Hasil penelitian menunjukkan bahwa prokrastinasi akademik dapat diatasi dengan meningkatkan regulasi diri, membuat rencana, menetapkan jadwal berdasarkan prioritas, mempersiapkan dengan matang, mengerjakan tugas langkah demi langkah, meningkatkan pengetahuan dan keterampilan, mengidentifikasi hambatan, memotivasi diri sendiri.